Efficacy of Three Remineralizing Agents on Erosion of Root Dentin by Cola Drink: An In Vitro Study - Ratanachina, Sirada; Pianmee, Chawalid; Nantanapiboon, Dusit; Poolthong, Suchit (European Journal of General Dentistry, 2024)
Objective The aim of the study was to investigate the effects of silver diamine fluoride (38% SDF), sodium fluoride (NaF) varnish, and casein phosphopeptide-amorphous calcium phosphate fluoride (CPP-ACPF) on cola-eroded root dentin microhardness and mineral alteration in vitro.Materials and Methods Forty human root dentin slabs were exposed to alternating 10 cycles of cola drink and artificial saliva, repeated 3 times at 6-hour intervals. Specimens were randomly assigned to four groups: control (deionized water), 38% SDF, NaF varnish, and CPP-ACPF. All specimens underwent the second erosion process. Microhardness was measured at baseline (KHN0), pretreatment (KHN1), and posttreatment (KHN2). The mean difference of microhardness (ΔKHN2-1) was analyzed using one-way analysis of variance (ANOVA) and Tukey's post hoc tests (α = 0.05). The chemical composition and surface morphology were assessed using energy dispersive spectroscopy (EDS) and scanning electron microscope (SEM).Results All experimental groups exhibited dentinal tubule occlusion. Both 38% SDF and NaF varnish demonstrated a statistically significant increase in microhardness compared to CPP-ACPF. However, CPP-ACPF was comparable to the control group. EDS analysis showed an increase in weight percentage of fluorine in all groups. Furthermore, silver and chlorine were detected in the 38% SDF group.Conclusion All treatments enhanced eroded root dentin microhardness, with 38% SDF and NaF varnish demonstrating superior acid resistance and preventing morphological changes induced by cola re-immersion.
Keywords: dental erosion; root dentin; surface hardness; cola drink; SDF; CPP-ACPF; sodium fluoride varnish